A high level of the long non-coding RNA MCF2L-AS1 is associated with poor prognosis in breast cancer and MCF2L-AS1 activates YAP transcriptional activity to enhance breast cancer proliferation and metastasis. Issue 5 (2nd May 2022) - She, Qing; Chen, Yuanyuan; Liu, Hong; Tan, Jichao; Li, Youhuai
ABSTRACT: Breast cancer (BC) is one of the most prevalent gynecologic malignant tumors with a poor prognosis and the second leading cause of cancer-related deaths in women worldwide. In recent years, it has been shown that long non-coding RNA (lncRNA) plays an important role in the development of breast cancer (BC). An antisense lncRNA from the MCF2 cell line (MCF2L-AS1) has been discovered recently and has been shown to function in a variety of malignancies. However, its function as a regulator of BC development has yet to be determined. Herein, the bioinformatics study analysis showed that MCF2L-AS1 was frequently highly expressed in BC tumors, and this overexpression was associated with worse patient outcomes. BC cells' proliferation, migration, and invasion are inhibited when MCF2L-AS1 is silenced, whereas the inverse is evident when MCF2L-AS1 is overexpressed. It was also observed that MCF2L-AS1 knockdown decreased carcinogenesis in xenograft tumor models. Furthermore, we discovered that MCF2L-AS1 could bind to and improve the transcription activity of the yes-associated protein (YAP). However, following YAP knockdown, this lncRNA's ability to drive BC malignancy was considerably reduced. In conclusion, MCF2L-AS1 may represent a potential predictive biomarker in BC patients, as well as a key regulator of BC cell proliferation. It works through positive feedback processes involving direct YAP binding and subsequent modulation of intracellular gene expression. Our findings add to our understanding of MCF2L-AS1 regulation and its potential as a therapeutic target in patients with this fatal cancer type. Graphical Abstract: uf0001